Dynamics of Anthropogenic Desertification of the European Desert on the Example of Russian Precaspian Region - Georgievna Lazareva, Victoria; Aleksandrovna Bananova, Valentina (International Journal of Engineering and Technology, 2018)
This article represents the results of multi-annual researches of desertification processes in droughty part of Europe - Russian Caspian Basin. Authors consider desertification as unification which leads to degradation of all components of arid ecosystems. It has been determined, that ecological-dynamic series of vegetational communities have the largest indicative value on quaternary terraces of Caspian Basin. They allow to trace the degradation sequence, to allocate the evaluation criteria and stages of desertification. Modern region vegetation is a result of cattle pasture and water management. It has been established that the vegetation of Late Khvalynian terrace on loamy soils is the most resistant to processes of degradation. The most vulnerable is young New Caspian. Cartographic materials confirm convertibility of desertification processes in semi-arid zone of European continent in response to natural-anthropogenic factors.Â Â
Keywords: Anthropogenic succession; Biological conception; Desertification; Indicators; Pasture degradation; Quatenary terraces; Unification; Vegetation